Corrosion inhibition of ferrite bainite AISI1040 steel in H2SO4 using biopolymer. Issue 1 (1st January 2021) - Prabhu, P.R.; Prabhu, Deepa; Chaturvedi, Ayush; Kishore Dodhia, Priyank
Abstract: The purpose of this study is to investigate the corrosion behavior of the ferrite-bainite phase of AISI1040 steel and its corrosion inhibition using pectin in 0.5 M sulphuric acid medium. The corrosion study was conducted through weight loss, potentiodynamic polarization, and electrochemical impedance spectroscopy (EIS) measurements. The study was conducted within the temperature range of 313–343 K and immersion time of 1 h— 7 h. The inhibition performance of pectin has boosted with an increase in the concentration of pectin and decreased with the temperature and time of exposure. From the weight loss study, the highest inhibition efficiency of 85% was achieved at 5.0 g/L at 1 h of exposure at 40 °C. The activation, thermodynamic, and adsorption isotherm were adapted for the experimental results. The energy and enthalpy of activation emphasized on energy barrier for the corrosion process. The entropy of activation values is negative, indicating the association of molecules. The physical adsorption of pectin on the metal surface was confirmed by the free energy of adsorption (close to-20kj mol −1 ). The enthalpy of adsorption indicated the exothermic process and, arrangement of the molecules on the surface of the metal expressed by the entropy of adsorption. The optimum efficiency of 74.9% is achieved for the addition of 5.0 g/L of pectin at 313 K by the EIS technique. Surface analyses involving a scanning electron microscope and atomic force microscopy were carried out to understand the nature of the surface in the presence and absence of pectin.